Djup icke vändande bearbetning i sockerbetsodling - Yngwe, Johan (2008)
A field experiment was carried out in 2006 to investigate the effects of deep rotary cultivation on sugarbeet growth. The background to the experiment was a 2005 study showing potentially higher yield, higher cleanness and higher sugar content when primary tillage was carried out to 35 cm depth with a rotary cultivator.